CAREER DEVELOPMENT CENTER (CDC) SEBAGAI STRATEGI UNGGULAN DALAM MEWUJUDKAN PENGEMBANGAN KARIR MAHASISWA DI UNIVERSITAS UDAYANA - Sihombing, Tulus P; Dwi Wismayanti, Kadek Wiwin; Sastra Wijaya, Komang Adi (CITIZEN CHARTER, 2019)
ABSTRACT Career Development Center (CDC) is a Career Development Center for students at Udayana University. This program aims to develop students' career and soft skills with various programs in order to improve the competency of Human Resources (HR). From the results of the SWOT analysis, it was found that the CDC has a problem in realizing a strategy focused on the issue of employee resources (HR), low budget funds and lack of facilities to support activities. Therefore researchers provide and recommend a New Public Management Managerial to streamline the realization of the CDC strategy. In realizing this New Managerial Public Management there are several indicators including, The Drive Orientation, Downsizing and Decentralization Orientation, Orientation in Search of Excellence, and Public Service Orientation, which emphasizes the quality, mission and values to be achieved by public organizations. Keywords: Strategy Management, Human Resource Management, New Public Managerial Management, CDC (Career Development Center)